Publicly available apps for cancer survivors: a scoping review - Peter Murchie; Rosalind Adam; Drew McMichael; Daniel Powell (BMJ Open)
Objectives To review the nature and scope of apps targeting individuals living with and beyond cancer.Design Scoping review, searching the two largest app stores, Google Play and Apple’s App store. App descriptions were exported verbatim, and summarised descriptively, thematically and by content coding.Results We included 151 apps targeting individuals living with and beyond cancer. Most targeted all cancer types (n=89, 58.9%) or breast cancer (n=22, 14.6%) and originated in the USA (n=68, 45.0%). The country of origin was unclear for 31 (20.5%) apps. Most apps were developed by commercial companies/private individuals (n=64, 43%) or non-profit organisations (n=30, 19.9%) and marketed apps in terms of fighting metaphors, navigating a journey and becoming empowered to take control.App content could be summarised under five main categories: (1) imparting information about cancer; (2) planning and organising cancer care; (3) interacting with others (including others affected by cancer and healthcare professionals); (4) enacting management strategies and adjusting to life with or beyond cancer and (5) getting feedback about cancer management, for example, by sharing self-monitoring reports with professionals. We found some apps describing ‘cures’ for cancer or selling products, such as alkaline waters to cancer survivors.Conclusions Apps are currently available via on-line stores that cover a large spectrum of cancer survivorship activities. The effects of such apps on clinical consultations, patient work/burden and clinical outcomes merit further attention. Most apps are developed by commercial organisations, and promises of empowerment in the ‘fight’ against cancer are tempered by the potential for exaggerated claims and exploitation.